Evolving therapeutic strategies for advanced hepatocellular carcinoma. (12th December 2021) - Qureshi, Ammar; Michel, Miguel; Lerner, Jaren; Dasanu, Constantin A.
ABSTRACT: Introduction: While sorafenib dominated the therapeutic arena in advanced hepatocellular carcinoma (HCC) for almost a decade, newer agents and combinations have been changing the therapeutic landscape in the last years. Areas covered: The authors outline the etiopathogenesis and evaluate the diagnostics in HCC, followed by a comprehensive review of the currently approved and experimental treatment approaches, with a focus on various systemic agents and combinations of agents. The manuscript was subdivided into relevant categories, thus making it applicable for both clinical practice and research endeavors. Expert opinion: Recently, combination therapies including immune checkpoint inhibitors with anti-VEGF/R agents have shown superior clinical efficacy in HCC. The Atezolizumab–bevacizumab combination is currently the preferred first-line therapy. Single-agents cabozantinib and regorafenib as well as nivolumab–ipilimumab combination are favored as second-line therapies. Further research is needed to identify the predictors of response to various treatments and establish the distinct patient profiles that will derive most benefit. Tumor mutation analysis and germline mutation testing could identify rational therapeutic targets in HCC in the near future. As the skyline for new therapeutic agents and combinations in HCC continues to expand, the outlook as of today is cautiously optimistic in this still difficult-to-treat malignant neoplastic disease.